Development and Clinical Implementation of a Hemostatic Balloon Device for Rectal Cancer Surgery. (June 2014) - Holman, Fabian A.; van der Pant, Noortje; de Hingh, Ignace H. J. T.; Martijnse, Ingrid; Jakimowicz, Jack; Rutten, Harm J.; Goossens, Richard H. M.
Background . Surgery for locally advanced and recurrent rectal carcinoma can be associated with major blood loss. Objective . We developed a promising technique using a hemostatic balloon to stop uncontrollable bleeding. Design . Models were developed using pelvic magnetic resonance imaging scans, and these models were tested in a cadaveric study. Eventually a model was tested in a clinical setting. The Hemostatic Balloon Device was placed in patients in whom during surgery uncontrollable bleeding from the venous presacral plexus occurred. Settings . A tertiary referral hospital for locally advanced and recurrent rectal cancer. Patients . Patients receiving multimodality treatment for primary or recurrent locally advanced rectal carcinomas. Main Outcome Measures . First the developed prototypes were tested in a cadaveric study where the developing pressure on the pelvic wall was measured. Second, the Hemostatic Balloon Device was placed in patients in whom during surgery uncontrollable bleeding from the venous presacral plexus occurred. Results . The balloon was used in 9 patients. Median volume of blood loss was 7500 mL. In 8 patients treatment with the hemostatic balloon was successful. In 1 patient the balloon was dislocated cranially and the pelvis was packed with surgical gauzes. Limitations . These first results are promising but further research is needed to evaluate how effective the balloon is in controlling massive bleeding during rectal cancer surgery. Future perspectives include a possibly thinner silicon rubber that can be stretched more easily with a lower inflated volume. Discussion . The hemostatic balloon is a new and promising technique for accomplishing hemostasis with controllable pressure on the pelvic cavity wall and can be removed without the need for a second laparotomy.